1986
DOI: 10.1161/01.res.58.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in ploidy levels and biochemical parameters in cardiac myocytes isolated from spontaneously hypertensive rats.

Abstract: Postnatal growth of the mammalian ventricular myocyte is characterized by a brief period of hyperplasia followed by an extensive period of physiological hypertrophy. Using myocytes isolated from both Wistar-Kyoto and spontaneously hypertensive rats from fetus to 10 months old, we analyzed morphological, biochemical, and ploidy changes. Fetal myocytes from both spontaneously hypertensive and Wistar-Kyoto rats were mononuclear, diploid cells. By 4 weeks, adult binucleation levels (84% binuclear) were found, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The third population with undetectable levels of expression corresponds to cells with indicator genes off in both nuclei. Previous studies (15) have shown that the vast majority (Ͼ91%) of the adult mouse cardiac myocytes are binucleate, and Engelmannn et al (31) have shown that multinucleate myocytes in the adult rat heart are least frequent in the left ventricle compared with the right ventricle and septum. Because our analyses were done exclusively in the left ventricle of the hearts, the relative contributions of the few mononucleate or multinucleate myocytes that may be present in the left ventricle are unlikely to have a major effect on our overall analyses and conclusions.…”
Section: Discussionmentioning
confidence: 95%
“…The third population with undetectable levels of expression corresponds to cells with indicator genes off in both nuclei. Previous studies (15) have shown that the vast majority (Ͼ91%) of the adult mouse cardiac myocytes are binucleate, and Engelmannn et al (31) have shown that multinucleate myocytes in the adult rat heart are least frequent in the left ventricle compared with the right ventricle and septum. Because our analyses were done exclusively in the left ventricle of the hearts, the relative contributions of the few mononucleate or multinucleate myocytes that may be present in the left ventricle are unlikely to have a major effect on our overall analyses and conclusions.…”
Section: Discussionmentioning
confidence: 95%
“…In animal experimentation of short-term pressure hypertrophy the myocardial adaptation has been found to consist of cellular enlargement with little or no DNA synthesis in the expanding myocytes (21,22), so that the possibility of nuclear and cellular hyperplasia has been severely questioned. Studies performed in humans, however, have indicated that when the heart is subjected to a prolonged and sustained load, hyperplasia ofmyocyte nuclei occurs (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Polyploidy is normally seen where cellular hypertrophy occurs with various cell types such as terminally differentiated cardiac myocytes, nonterminally differentiated hepatocytes, and smooth muscle cells. [50][51][52][53] Polyploidy in human artery wall smooth muscle cells ranged from 1 to 7% of the SMC population depending on the age of the subject. 54 While polyploidy can lead to altered gene expression in yeast 55 the functional significance of polyploidy is unknown in SMC.…”
Section: A B C Dmentioning
confidence: 99%